Ambient sulfur dioxide levels associated with reduced risk of initial outpatient visits for tuberculosis: A population based time series analysis. (September 2017) - Ge, Erjia; Fan, Min; Qiu, Hong; Hu, Howard; Tian, Linwei; Wang, Xiaomeng; Xu, Guozhang; Wei, Xiaolin
Abstract: Background: Recent biochemical studies suggest that exogenous sulfur dioxide (SO2 ) at low concentrations may have been beneficial in inhibiting mycobacteria tuberculosis (TB) growth. However, there is a dearth of population-based studies. Objectives: To examine the association of ambient SO2 levels and initial TB outpatient visits. Methods: In Ningbo, China, we collected all daily initial outpatient visits for TB and routinely air pollution monitoring data between January 2009 and December 2013. A time-series study was conducted by using generalized additive regression (GAM) with log-linear Poisson models to estimate the associations between daily initial TB outpatient visits and daily average concentration of SO2. Other traffic-related co-pollutants were adjusted. Sensitivity analyses were conducted to examine the relationship when 1% extreme SO2 concentrations excluded or if related to the early onsets of TB symptoms. Results: SO2 concentrations in Ningbo were low with a daily average of 25 μg/m 3 (i.e. 0.0089 ppm). Negative associations were identified between ambient SO2 concentrations and daily initial TB outpatient visits. A 10 μg/m 3 increase in SO2 at lag3 and lag0-3 days were associated with −2.0% (95%CI,  −3.2,  −0.8) and −4.6% (95%CI,  −6.8,  −2.4) changes, respectively, in initial TB outpatient visits according to single-pollutant models. The negative association became stronger when nitrogen dioxide (NO2 ) or particulate matter with aerodynamic diameter less than 10 μm (PM10 ) was adjusted in two-pollutant models. This association was higher in males vs. females and in middle-aged adults vs. the elderly. We found a stronger negative association between SO2 concentration and the initial symptom occurrence. Conclusion: Short-term exposure to ambient SO2 was associated with reduced risk of initial TB outpatient visits, suggesting acute protective effects of low-level ambient SO2 exposure on bacteria-induced pulmonary infections. Graphical abstract: